2023
DOI: 10.3390/cells12020284
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β2-Adrenergic Receptors in Microglia Alleviates Neuropathic Hypersensitivity in Mice

Abstract: Drugs enhancing the availability of noradrenaline are gaining prominence in the therapy of chronic neuropathic pain. However, underlying mechanisms are not well understood, and research has thus far focused on α2-adrenergic receptors and neuronal excitability. Adrenergic receptors are also expressed on glial cells, but their roles toward antinociception are not well deciphered. This study addresses the contribution of β2-adrenergic receptors (β2-ARs) to the therapeutic modulation of neuropathic pain in mice. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Chronic pain can have different aetiologies. This Special Issue discusses, for example, chronic pain due to nerve injury [ 4 , 5 ], chronic pain associated with a genetic disease [ 6 ], or chronic pain associated with cancer [ 7 ]. Hirth et al characterized two mouse models (KPC and KPPC models) based on the most common genetic alteration found in human pancreatic cancer tissues (i.e., p53 and Kras) and suitable to study pain associated with pancreatic ductal adenocarcinoma (PDAC), the most prevalent type of pancreatic cancer [ 8 , 9 ].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Chronic pain can have different aetiologies. This Special Issue discusses, for example, chronic pain due to nerve injury [ 4 , 5 ], chronic pain associated with a genetic disease [ 6 ], or chronic pain associated with cancer [ 7 ]. Hirth et al characterized two mouse models (KPC and KPPC models) based on the most common genetic alteration found in human pancreatic cancer tissues (i.e., p53 and Kras) and suitable to study pain associated with pancreatic ductal adenocarcinoma (PDAC), the most prevalent type of pancreatic cancer [ 8 , 9 ].…”
mentioning
confidence: 99%
“…Modulation of inflammatory signaling was also found in a model of chronic pain induced by nerve injury [ 5 ]. Using a new conditional mouse line, which loses ß2-AR exclusively in microglial cells, Damo et al demonstrated that specific activation of the microglial ß2 adrenergic receptor can modulate nerve injury-associated neuropathic pain by inducing a structural and functional change in microglial cells compared with an activated state associated to the nerve injury model used in the study (spared nerve injury, SNI) [ 5 ]. Interestingly, this alteration of microglia was associated, at least in vitro, with changes in cytokine release [ 5 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations